2022
DOI: 10.1002/advs.202202048
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Layered Ferroelectrics with Global C∞v Symmetry

Abstract: Ferroelectricity in fluid materials, which allows free rotation of molecules, is an unusual phenomenon raising cutting‐edge questions in science. Conventional ferroelectric liquid crystals have been found in phases with low symmetry that permit the presence of spontaneous polarization. Recently, the discovery of ferroelectricity with high symmetry in the nematic phase has attracted considerable attention. However, the physical mechanism and molecular origin of ferroelectricity are poorly understood and a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 29 publications
(37 reference statements)
1
51
0
Order By: Relevance
“…Here we design two highly rigid and fluorinated polar LC molecules with intrinsically large dipolar moment (>14 D) and introduce a new ferroelectric orthogonally lamellar LC phase, dubbed the ferroelectric smectic A (SmA F ) phase, right beneath the N F state (Figure ). Within the SmA F layers, the local polarization is along the long axis of molecules as similarly reported by Kikuchi et al and Chen et al very recently. It is revealed that the SmA F materials represent enhanced polarization properties, e.g., higher coercivity field ∼3.0 V μm –1 , remnant and saturated polarizations, i.e., ∼6.5 μC cm –2 , than the N F materials.…”
supporting
confidence: 79%
“…Here we design two highly rigid and fluorinated polar LC molecules with intrinsically large dipolar moment (>14 D) and introduce a new ferroelectric orthogonally lamellar LC phase, dubbed the ferroelectric smectic A (SmA F ) phase, right beneath the N F state (Figure ). Within the SmA F layers, the local polarization is along the long axis of molecules as similarly reported by Kikuchi et al and Chen et al very recently. It is revealed that the SmA F materials represent enhanced polarization properties, e.g., higher coercivity field ∼3.0 V μm –1 , remnant and saturated polarizations, i.e., ∼6.5 μC cm –2 , than the N F materials.…”
supporting
confidence: 79%
“…1). 25 Therefore, it is necessary to evaluate the effect of structural variations on dipole moments, LC phases, and ferroelectricity in detail. Therefore, we synthesized various structured C3-DIO analogues, which are shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Under this circumstance, the control of the phase sequences involving the N F emergence and the successful way of stabilizing N F remain ambiguous despite huge efforts on the design and development of new N F LC molecules based on molecular parameters. Note that a newfound ferroelectric state, that is, a uniaxial ferroelectric smectic A (SmA F ) phase 37,38 that appears just below the N F phase, just emerged, offering an important clue. SmA F looks highly correlated with the N F phase; hence, the smectic cluster floating in the N F media may influence the N F phase characteristic.…”
mentioning
confidence: 99%